Entrepreneurial Interest and Career Development of Vocational High School Graduates Fashion Design in the Digital Era - Vitariyanti, Diyan; Cahyono, Budi Tri; Pambudi, Nugroho Agung; Efendi, Agus (Universitas Sebelas Maret, 2024)
Fashion design skills can be developed through classroom training and during industry placements. In the era of Industry 4.0, the focus on human capital underscores their readiness, skills, investment (especially in human resources), and proficiency in digital services. The aim study is to identification the interest and career development of SMK Tata Busana graduates in the digital era. This research uses qualitative research approach. Collect data is including interviews, observations, examination of documents or archives, and conducting tests. A triangulation method is applied, which relies on references. The result is The interests entrepreneurship and career development of SMK Fashion students in this digital era can be directed Fashion entrepreneurship among vocational school students Fashion Design usually shows a tendency to increase activity, creativity, and innovation. The career interests of SMK Fashion students that can be developed in this digital era include their capacity to use digital technology effectively, understand the functions of various applications, understand the principles of digital security, and solve technical problems that may arise. SMK as an educational institution plays an important role in honing students' abilities in digital services by providing training programs that are in line with the demands of the digital era job market.